Use of artificial intelligence by companies in Germany : prevalence and enabling factors - Gerhards, Christian [Verfasser]; Baum, Myriam [Verfasser] (My University, 2024)
"Against the background of current breakthroughs in machine learning and in light of the reignited debate regarding the substitutability of human work, data from the BIBB Establishment Panel on Training and Competence Development (BIBB Training Panel) is being used to investigate the extent to which the use of artificial intelligence (AI) by companies in Germany has increased over recent years and to examine in which companies AI is used particularly frequently." (authors' abstract; BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; G 2.2.1 Technologisierung; 370; Arbeitsmarktentwicklung; Substitution; Künstliche Intelligenz; Betrieb; Technische Entwicklung; BIBB-Qualifizierungspanel